An Overview of Filter Integrated Switch (FIS) for RF and Microwave Applications - Shairi, N.A. (Universiti Teknikal Malaysia Melaka, 2018)
Integrating multiple devices into one single device is an effective method to reduce circuit size, mismatching loss, and fabrication cost. Radio frequency (RF) and microwave device integrated with filter have become a popular design concept in the recent years. In this paper, an overview of the filter integrated switch (FIS) for RF and microwave applications is presented based on previously published studies and research journals starting from 2006 until 2016. This paper also emphasizes the use of previous and current development of filter integrated switches which mainly covers the fundamental concept on the FIS, the research trends in designs and developments. At the end, this paper reports on the variety of applications that can greatly benefit from FIS and some challenges and factors that need to be considered in designing and development of filter integrated switches. Â© 2018 Universiti Teknikal Malaysia Melaka. All rights reserved.